Cognitive flexibility in a generalist raptor: a comparative analysis along an urbanization gradient - Biondi, Laura Marina (2024)
In this study, we analyzed the variation in cognitive flexibility in the Chimango Caracara (Milvago chimango), across areas with different levels of urbanization. To assess this, we utilized the reversal learning assay which measures the ability to adapt behavior in response to changes in environmental contingencies. We also investigated the impact of neophobia on this variation. All chimangos studied succeeded in acquiring a color-reward association and reverting this learned association when the contingencies changed. Urban chimangos were faster than their rural and suburban counterparts during the initial discrimination and reversal phases. The reversal phase proved to be the most challenging task. The analysis of the errors made during this phase revealed that acquiring a new association (i.e., regressive errors) was challenging for the individuals studied, in comparison to inhibiting a previously learned one (i.e., perseverative errors). Neophobia was found to be lower in urban individuals compared to suburban and rural raptors. Moreover, neophobia showed a correlation with regressive errors during the reversal phase among rural and suburban chimangos, while no such correlation was observed among city-dwelling chimangos. We suggest that neophobia acted as a regulating factor of cognitive flexibility, mainly for individuals expressing relatively high levels of this personality trait.